2023
DOI: 10.1002/batt.202200421
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State NMR Study on the Structure and Dynamics of Graphite Electrodes in Sodium‐Ion Batteries with Solvent Co‐Intercalation

Abstract: The possibility to co-intercalate sodium ions together with various glymes in graphite enables its use as a negative electrode material in sodium-ion batteries (SIBs). However, the storage mechanism and local interactions appearing during this reaction still needs further clarification. 1 H, 13 C and 23 Na ex situ solid-state NMR (ss-NMR) experiments are performed to obtain insights into the storage mechanism depending on the state of charge (SOC) and the electrolyte solvent used. Distinct differences could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
(138 reference statements)
2
8
1
Order By: Relevance
“…The signal at 123-126 ppm is assigned to the graphitic carbon adjacent to a solvated sodium ion layer in agreement with previous studies. [42,51] The decrease in line width for the THF/2G electrolyte compared to pure 2G indicates a loss in mobility for the THF/2G electrolyte, which corroborates its lower rate capability (see Figure S4). This is pushed to the extreme for pure THF, where only a very broad peak is visible in the same graphitic carbon region.…”
Section: Ex Situ Solid-state Nmr Spectroscopymentioning
confidence: 60%
See 2 more Smart Citations
“…The signal at 123-126 ppm is assigned to the graphitic carbon adjacent to a solvated sodium ion layer in agreement with previous studies. [42,51] The decrease in line width for the THF/2G electrolyte compared to pure 2G indicates a loss in mobility for the THF/2G electrolyte, which corroborates its lower rate capability (see Figure S4). This is pushed to the extreme for pure THF, where only a very broad peak is visible in the same graphitic carbon region.…”
Section: Ex Situ Solid-state Nmr Spectroscopymentioning
confidence: 60%
“…Several NMR studies have indicated that at full sodiation, there are both free and bound solvents inside the graphite galleries, and a recent paper by Escher et al indicate that there are 2-3 2G molecules per Na + in the graphite at full sodiation. [18,42] This would indicate that roughly 1.2-1.8 μl of 2G is needed per mg of graphite. Thus, an electrode with a radius of 12 mm and a loading of 9 mg/cm 2 requires in the range of 12-18 μl of 2G at full sodiation.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Recently, studies have shown a method of cointercalation with solvent molecules, which, however, in a solid electrolyte battery is not applicable. 13,14 For sodium ASSB studies, sodium metal is used most commonly as the anode material. 11,15 The use of sodium as anode is most attractive for maximizing the energy density of the cell, but its application is difficult for the same reasons that are known from lithium.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The Na + ion ( r (Na + ) = 102 pm) has a larger ion radius than Li + ( r (Li + ) = 76 pm), and its intercalation into the graphite layered structure has been perceived thermodynamically impossible . Recently, studies have shown a method of cointercalation with solvent molecules, which, however, in a solid electrolyte battery is not applicable. , For sodium ASSB studies, sodium metal is used most commonly as the anode material. , The use of sodium as anode is most attractive for maximizing the energy density of the cell, but its application is difficult for the same reasons that are known from lithium. In particular, side reactions with the solid electrolyte and the formation of dendrites during charging remain key challenges.…”
Section: Introductionmentioning
confidence: 99%